2018
DOI: 10.5194/bg-15-2361-2018
|View full text |Cite
|
Sign up to set email alerts
|

Interannual drivers of the seasonal cycle of CO<sub>2</sub> in the Southern Ocean

Abstract: Abstract. Resolving and understanding the drivers of variability of CO 2 in the Southern Ocean and its potential climate feedback is one of the major scientific challenges of the ocean-climate community. Here we use a regional approach on empirical estimates of pCO 2 to understand the role that seasonal variability has in long-term CO 2 changes in the Southern Ocean. Machine learning has become the preferred empirical modelling tool to interpolate time-and locationrestricted ship measurements of pCO 2 . In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 74 publications
(156 reference statements)
5
89
2
Order By: Relevance
“…Both Southern Ocean pCO 2 and SAM spectra are however the only two that illustrate a maximum between 10 and 15 years. This is in agreement with observed variations from recent study investigating the CO 2 variability south of Tasmania based on in situ measurements (Xue et al, 2018), whereas a study by Gregor et al (2018) suggests that modes of summer variability are substantially smaller in the Southern Ocean. While the anomaly time series between the pCO 2 and the SAM index exhibit low correlations (R = 0.01), the power spectrum suggests a moderate link (R = 0.35) between the two.…”
Section: Resultssupporting
confidence: 92%
“…Both Southern Ocean pCO 2 and SAM spectra are however the only two that illustrate a maximum between 10 and 15 years. This is in agreement with observed variations from recent study investigating the CO 2 variability south of Tasmania based on in situ measurements (Xue et al, 2018), whereas a study by Gregor et al (2018) suggests that modes of summer variability are substantially smaller in the Southern Ocean. While the anomaly time series between the pCO 2 and the SAM index exhibit low correlations (R = 0.01), the power spectrum suggests a moderate link (R = 0.35) between the two.…”
Section: Resultssupporting
confidence: 92%
“…The majority of models have pCO 2 biases, and reducing these biases is an active area of research (see Jiang et al, 2014;Mongwe et al, 2018). Recent studies demonstrate that models that accurately reproduce pCO 2 on seasonal time scales are more skillful at capturing pCO 2 variability on longer time scales and are therefore important for climate change simulations (Gregor et al, 2018;Gruber et al, 2019). In order to diagnose these model biases, validation studies have focused on examining the modeled versus observed pCO 2 decomposition, comparing the seasonal cycles of total pCO 2 , pCO 2(T) , and pCO 2(nonT) (demonstrated in section 3.4).…”
Section: Utility Of the Dpt As A Model Metricmentioning
confidence: 99%
“…Our current understanding of the drivers of CO 2 flux in the Southern Ocean is limited to a few observation-based studies which are heavily weighted toward the Drake Passage Time-series (DPT; Gregor et al, 2018;Fay et al, 2018;Landschützer et al, 2015;. The variability in the strength of the Southern Ocean carbon sink on seasonal time scales is largely driven by compensatory variations in temperature, biology, and vertical exchange with the enriched deep waters, which in turn, drive variability on interannual time scales (Gregor et al, 2018;Takahashi et al, 1993). The DPT is the only multiyear, year-round ship-based biogeochemical sampling program in the Southern Ocean and, in particular, the ACC.…”
Section: Introductionmentioning
confidence: 99%
“…The surface ocean pCO 2 observations from the DPT have provided the foundation for larger datasets, which have been extensively used to examine variability and trends in CO 2 uptake in the broader Southern Ocean (Fay and McKinley, 2013;Majkut et al, 2014;Landschützer et al, 2014bLandschützer et al, , 2015bRödenbeck et al, 2015, Gregor et al, 2018. In many of these studies, interpolated estimates of Southern Ocean pCO 2 are used in conjunction with measurements of atmospheric pCO 2 to estimate variability and trends in the air-sea pCO 2 gradient and, when combined with wind speed, air-sea CO 2 fluxes.…”
Section: Introductionmentioning
confidence: 99%